Class of antipsychotic and duration of psychiatricinpatient treatment: an 8-year ecological study - Balan , Alexandre Balestieri (2018)
Objective: Studies have shown changes in antipsychoticprescription patterns over the last two decades, withemphasis on the increased use of atypical antipsychoticsas compared to typical ones. The objective of this studywas to longitudinally evaluate trends in the prescriptionof typical and atypical antipsychotics (except clozapine)and their association with the mean length of stay in apsychiatric hospital. Methods: This was an ecological study. The pharmacyand the Medical Archive and Statistics Service ofInstituto de Psiquiatria de Santa Catarina provided dataon antipsychotic prescriptions and mean hospital stayfrom January 2007 to December 2014. Simple andmultiple linear regression analyses were used to evaluatethe association between independent variables and theoutcome.Results:Over the 8 years of study, there was anincrease in the prescription of atypical antipsychotics(coefficient B = 0.0037; 95% confidence interval [95%CI]0.0033 to 0.0041; p < 0.001) and a reduction in theprescription of typical antipsychotics (coefficient B =-0.009; 95%CI -0.01 a -0.008; p < 0.001), measuredin defined daily doses (DDD). There was no associationbetween prescription of typical/atypical antipsychoticsand mean monthly hospitalization stay. There was anincrease in hospital occupancy rate in the period, withfrequent overcrowding. Conclusion: The worldwide pattern of increasedprescription rates of atypical antipsychotics was alsofound in this study. There was no association betweenthis increase and mean length of hospital stay. Althoughthis was not an objective of this study, the overcrowdingobserved deserves the attention of public managers.